ANALISIS DETERMINAN GRAPHICAL INFORMATION DISCLOSURE SEBAGAI PENDUKUNG PRINSIP TRANSPARANSI PERUSAHAAN PUBLIK DI INDONESIA - Purwanto, Agus (JURNAL AKUNTANSI DAN AUDITING, 2010)
Managements report the graphical information disclosure toward multi user to decision making.The graphical information disclosure is consist of: sale, revenue, income, equity, asset, liabitity,cash, and expense. This research gets 56 firm that have financial reporting with graphicalinformation disclosure index 49,5%. The research gets result that all of the firm characteristicsdon’t have effect of graphical information disclosure index. Graphical information disclosuretowards understand of financial reporting better and effective.